(untitled) (Progress Annals: Journal of Progressive Research, 2026)
This article examines the principles of creating an electronic linguistic database of translation units in literary texts within the framework of Uzbek corpus linguistics. The study focuses on the methodological foundations of corpus creation, including segmentation, annotation, and alignment processes. Special attention is given to the development of Uzbek language corpora and their role in translation studies and computational linguistics. The research demonstrates that corpus-based approaches provide effective tools for identifying and systematizing translation units. The results highlight the importance of empirical data in improving translation quality and developing linguistic resources